2022
DOI: 10.3390/nu14235093
|View full text |Cite
|
Sign up to set email alerts
|

Role of Residence Area on Diet Diversity and Micronutrient Intake Adequacy in Urban and Rural Costa Rican Adolescents

Abstract: Dietary diversity might be essential to meet nutritional demands during adolescence. Diet diversity among 818 urban and rural Costa Rican adolescents aged 13–18 years was studied using the Minimum Dietary Diversity Score for Women. The Nutrient Adequacy Ratio (NAR) was calculated for 11 nutrients to estimate the nutrient adequacy of the diet. A NAR < 0.7 was considered inadequate for micronutrient intake. The optimal Diet Diversity Score (DDS) cut-off point for this study was 4, established using receiver-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…Similarly, MDD-W (i.e., ≥5 food groups) showed the best predictive capacity for an MPA > 0.60 among children (2–9 y) in China, whereas ≥6 food groups performed more adequately among adolescents, women, men, and the elderly (≥10 y) [ 22 ]. Lastly, among adolescents (13–18 y) in Costa Rica, ≥4 food group threshold best predicted a MAR of ≥0.70 [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, MDD-W (i.e., ≥5 food groups) showed the best predictive capacity for an MPA > 0.60 among children (2–9 y) in China, whereas ≥6 food groups performed more adequately among adolescents, women, men, and the elderly (≥10 y) [ 22 ]. Lastly, among adolescents (13–18 y) in Costa Rica, ≥4 food group threshold best predicted a MAR of ≥0.70 [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…A diverse diet becomes especially relevant during adolescence since, at this stage of life, nutrient requirements are notably high due to physical growth and biological maturation [1]. Various studies have shown that adolescents living in low-and middleincome countries have low dietary diversity and poor consumption of micronutrient-dense foods, leading to a high prevalence of inadequate intakes of vitamin A, iron, calcium, zinc, and folates [2][3][4][5][6][7], as well as a high prevalence of vitamin B12 deficiency, low serum zinc, and anemia [3].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary diversity scores have been identified as promising measurement tools due to their simplicity of implementation compared to other complex and expensive methods used to monitor micronutrient intake [15]. Although it was validated and intended to be used as a proxy for micronutrient adequacy in women of reproductive age, the Minimum Dietary Diversity for Women (MDD-W) has shown its applicability in other population groups, including adolescents [5,6,18,19]. To simplify the use of the MDD-W, dichotomous versions of it have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…However, considering the high prevalence of overweight/obesity among adolescents, the high consumption of added sugars, and the potentially significant amount of vit-A that added sugars could provide, a paradox arises for Costa Rican public health to reduce or prevent obesity during adolescence. Lowering the added sugar intake to less than 10% TEI could lead to a markedly inadequate vit-A intake in adolescents, especially since adolescents are poor consumers of animal food sources of vit-A and vit-A-rich fruits and vegetables [ 12 ].…”
Section: Introductionmentioning
confidence: 99%